Frailty and Geriatric Medicine During the Pandemic - Crosignani, Silvia; Fantinati, Jacopo; Cesari, Matteo (Frontiers in Medicine, 2021)
The term frailty in the era of COVID-19 has a manifold implication. The vast majority of the countries worldwide being hit by the pandemic have showed the frailty of their health and social care systems. Although the surprise factor could somehow justify the unpreparedness experienced during the first wave, the second wave still led to significant difficulties almost everywhere. Looking at Italy's situation, it is evident how the stress test applied by COVID-19 on the system has threatened its stability, getting it closer to collapsing many times. It is true that Italy, in particular the Northern regions, has been the epicenter of COVID-19 in Europe in a time when information about the SARS-CoV-2 was still lacking and confused. Nevertheless, what happened has demonstrated significant issues in the structure, priorities, and organization of the system. It has exemplified the obsolete approach adopted in clinical practice, particularly when applied to frail older persons. The COVID-19 pandemic has made emerging the need for a substantial reshaping of our healthcare system. The hospital-centered model has dramatically failed. To adequately face the new challenges brought by the increasing complexity of our aging society, it is critical to move the barycenter of action towards the community/primary care, promoting the integration of services and centralization of clinical/administrative data. It is vital to train healthcare professionals in the identification and basic principles of geriatric conditions, clarifying the role that geriatricians play.